PERANCANGAN BUKU PANDUAN INTERAKTIF MENGENAI PENGENALAN PENYAKIT GANGGUAN KELENJAR TIROID PADA ANAK-ANAK - DENISE KEMAS; ELIZABETH WIANTO; MIKI TJANDRA (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
The danger of thyroid disease disorder can be suffered by anyone, including in children aged 7 to 12 years old. If not treated immediately, this disease can have a fatal impact of heart failure, prominent eyes, mental health, and sterility, even to a coma. This happens because of a lack of knowledge about the thyroid gland, its illness and its dangerous effect, which leads to less information given to the children about the disorder. The aim of this design of this interactive guidebook is so that parents and children can know and start tackling about the thyroid gland as well as the dangers of this disease and want to start a healthy lifestyle, by starting to eat healthy foods for the thyroid gland. Visual communication strategy used is to create an educative and interactive guidebook. Supported by supporting media, such as: workbook, promotion media that is booth, leaflet, poster, website and gimmick. The final goal of the design is that parents and children can recognize the thyroid gland and maintain their health by eating a healthy diet and live a healthy lifestyle.Â Keywords:Â children; guidebook; interactive; thyroid disorder